Emission and Accumulation of Monoterpene and the Key Terpene Synthase (TPS) Associated with Monoterpene Biosynthesis in Osmanthus fragrans Lour - Zeng, Xiangling; Liu, Cai; Zheng, Riru; Cai, Xuan; Luo, Jing; Zou, Jingjing; Wang, Caiyun (Frontiers in Plant Science, 2016)
Osmanthus fragrans is an ornamental and economically important plant known for its magnificent aroma, and the most important aroma-active compounds in flowers are monoterpenes, mainly β-ocimene, linalool and linalool derivatives. To understand the molecular mechanism of monoterpene production, we analyzed the emission and accumulation patterns of these compounds and the transcript levels of the genes involved in their biosynthesis in two O. fragrans cultivars during flowering stages. The results showed that both emission and accumulation of monoterpenes varied with flower development and glycosylation had an important impact on floral linalool emission during this process. Gene expression demonstrated that the transcript levels of terpene synthase (TPS) genes probably played a key role in monoterpene production, compared to the genes in the MEP pathway. Phylogenetic analysis showed that OfTPS1 and OfTPS2 belonged to a TPS-g subfamily, and OfTPS3 and OfTPS4 clustered into a TPS-b subfamily. Their transient and stable expression in tobacco leaves suggested that OfTPS1 and OfTPS2 exclusively produced β-linalool, and trans-β-ocimene was the sole product from OfTPS3, while OfTPS4, a predictive sesquiterpene synthase, produced α-farnesene. These results indicate that OfTPS1, OfTPS2, and OfTPS3 could account for the major floral monoterpenes, linalool and trans-β-ocimene, produced in O. fragrans flowers.